A numerical CFD simulation method using static grid based on momentum compensation for screw pumps. Issue 1 (September 2021) - Yan, Di; Tang, Qian
Abstract: Three-dimensional CFD numerical simulation is the most powerful tool for performance analysis of screw machines. This paper compares and analyzes two CFD numerical calculation methods based on moving and static grid, and proposes a static grid calculation method based on momentum compensation, which takes into account the wall velocity and fluid momentum on the rotor surface when the screw rotor rotates. That is, while the static grid is used, the rotation characteristics of the fluid domain between the rotors are considered. Compared with the commonly used static grid method, this method greatly improves the accuracy of the calculation, the calculation error of mass flow rate is reduced from 2.32% to 1.14%. At the same time, it is simple and easy to implement. It is also suitable for modelling screw machines with special-shaped rotors, which are still challenge for moving grids. The accuracy and reliability of the method are verified by comparison with the calculation results of the moving grid and the experiments.